Molecular Motor KIF3B Acts as a Key Regulator of Dendritic Architecture in Cortical Neurons - Joseph, Nadine F.; Grinman, Eddie; Swarnkar, Supriya; Puthanveettil, Sathyanarayanan V. (Frontiers in Cellular Neuroscience, 2020)
Neurons require a well-coordinated intercellular transport system in order to maintain its extensive cyto-architecture. The kinesin family of proteins (KIFs) fills this role by regulating the transport of a diverse array of cargos in post-mitotic cells. On the other hand, in mitotic cells, KIFs facilitate the fidelity of the cellular division machinery. Though certain mitotic KIFs also have function in post-mitotic neurons, little is known about them. Therefore, we studied the role of a mitotic KIF, (KIF3B) in neuronal architecture. We find that the RNAi mediated knockdown of KIF3B in primary cortical neurons resulted in an increase in spine density, number of thin and mushroom spines as well as dendritic branching. Consistent with the change in spine density, we observed a specific increase in the distribution of the excitatory post-synaptic protein, PSD-95 in KIF3B knockdown neurons. Interestingly, the overexpression of KIF3B produced a reduction in dendritic branching. Taken together, these studies suggest that KIF3B is a key determinant of cortical neuron morphology and that it functions as an inhibitory constraint on structural plasticity, further illuminating the significance of mitotic KIFs in post-mitotic neurons.